2021
DOI: 10.3390/nu13061774
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-Rich Lipoproteins and Their Remnants as Silent Promoters of Atherosclerotic Cardiovascular Disease and Other Metabolic Disorders: A Review

Abstract: While targeting elevated serum levels of low-density lipoprotein cholesterol has been the mainstay of atherosclerosis prevention and treatment for decades, the evidence regarding the atherogenic role of hypertriglyceridemia is still controversial. Various epidemiological population-based studies on statin-treated subjects nominated triglycerides, triglyceride-rich lipoproteins (namely, chylomicrons and very-low-density lipoprotein particles), and their remnants as major determinants of the substantial residual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 84 publications
0
15
0
2
Order By: Relevance
“…Several studies have shown that a high level of triglycerides contributes to atherosclerosis (35)(36)(37), while a low level is a risk factor for cerebral hemorrhage (38). It was also reported that a low level of triglycerides was a modest risk factor for HT after IVT (11).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that a high level of triglycerides contributes to atherosclerosis (35)(36)(37), while a low level is a risk factor for cerebral hemorrhage (38). It was also reported that a low level of triglycerides was a modest risk factor for HT after IVT (11).…”
Section: Discussionmentioning
confidence: 99%
“…Postprandial lipemia has been shown to be associated with increased oxidative stress and decreased FMDs in healthy, male participants ( 22 ). Circulating triglyceride-rich lipoproteins and their remnants are also associated with endothelial dysfunction and CVD risks ( 172 , 173 ). This work showed that the percentage fat content of the meals was inversely associated with the postprandial change in FMD at 3 hours, indicating a reduced vessel response as the fat percentage increased.…”
Section: Discussionmentioning
confidence: 99%
“… 17–20 According to Sascău et al, triglyceride-rich lipoproteins and their remnants are silenced promoters of atherosclerotic cardiovascular disease and other metabolic diseases. 38 Hadi et al reported that RC is associated with prediabetes, and they suggested that RC might have a certain influence on glucose metabolism. 39 However, the nature of the relationship of RC with new-onset diabetes is unclear, and in this context, the present study investigated the association between them.…”
Section: Discussionmentioning
confidence: 99%